Analisis Dan Pengukuran Tingkat Kematangan Manajemen Layanan Teknologi Informasi Pada Aplikasi Mytelkomsel Menggunakan Framework ITIL V3 - Fian Puspita Sari; Sofia Alfiona Rizki (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze and measure the maturity level of information technology service management in the MyTelkomsel application using the ITIL V3 framework, focusing on the Service Operation domain. The method used was descriptive quantitative, using a questionnaire containing 15 questions representing the five main ITIL V3 processes, distributed to 54 MyTelkomsel users. The test results showed the instrument was valid and reliable. Data analysis showed that all processes were at Level 4 (Managed) with an average score of 3.89, indicating that IT service management has been implemented consistently, documented, and measured according to ITIL V3 practices. However, improvement to Level 5 (Optimized) is still needed through process automation, strengthening access security, and implementing continuous evaluation to improve service quality.